Patriarki birokratik: Identitas perempuan dalam praktik penyebutan nama dan jabatan suami di organisasi militer - Kusumo, Yudhy Widya; Sari, Eka Anisa; Chotijah, Siti (Program Studi Ilmu Komunikasi UII, 2026)
This study aims to explore how communication practices, particularly the mention of husbands' names and titles, shape women's identities within military wives' organizations in Indonesia. Within this organizational structure, women's personal identities are often reduced to secondary identities related to their husbands' positions. Using Sara Mills' critical discourse analysis, this study examines the roles of subject and object, as well as the representation of women in organizational discourse. Data were collected through in-depth interviews with soldiers' wives across ranks and through observations of symbolic interactions on social media. The results show that the practice of mentioning husbands' names and titles functions as a form of symbolic violence that fragments women's authentic identities. This phenomenon creates a condition in which women become